(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
This article will analyze forms of representation of the Patagonia in the novel Patagonia Express by the Chilean author Luis Sepulveda. Characterized by intertextuality as well as aspects of the sentimental novel, these travel tales of the Patagonia are structured as narratives by spaces of the imagination. These spaces are designed to seduce the reader, installing him in a mysterious space, both legendary and historical; whose passionate exploration will create a strong bond between text and reader. Our hypothesis is that the Patagonia of Patagonia Express is not a space established by its referent; rather, the emphasis is upon revisiting and revitalizing originative legends and texts. Because of this attachment to literary constructions, descriptions of the referent allow the reader to be influenced by stereotypes of the foundational text.